2002
DOI: 10.1111/j.1939-1676.2002.tb02408.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Cerebellar Ataxia in Coton de Tulear Dogs

Abstract: A neonatal ataxia syndrome was observed in Coton de Tulear dogs. Seven affected pups (32%; 7/22) of both genders came from 5 different litters with phenotypically normal parents. Neurologic examination revealed normal mental status, head titubation, intention tremors, and severe gait, stance, and ocular ataxia beginning at 2 weeks of age. One of the pups was able to walk with assistance, but most of the affected pups were unable to stand and used propulsive movements (''swimming'') for goal-oriented activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…21,22 Similar pathology may explain the subtle ultrastructural abnormalities reported in the cerebellar molecular layer from a 4-month-old puppy with BNAt. 1 Electrophysiologic experiments with brain sections from Grm1 knockout mice have demonstrated deficiencies in long-term depression in the cerebellum and deficiencies in long-term potentiation in the hippocampus. 6,7,23 Longterm depression and long-term potentiation are widely believed to be the bases for learning and memory.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21,22 Similar pathology may explain the subtle ultrastructural abnormalities reported in the cerebellar molecular layer from a 4-month-old puppy with BNAt. 1 Electrophysiologic experiments with brain sections from Grm1 knockout mice have demonstrated deficiencies in long-term depression in the cerebellum and deficiencies in long-term potentiation in the hippocampus. 6,7,23 Longterm depression and long-term potentiation are widely believed to be the bases for learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Pedigree analysis suggested an autosomal recessive mode of inheritance for BNAt. 1 An apparently distinct, later-onset cerebellar ataxia of Coton de Tulear puppies with granule cell degeneration also has been described. We here report that a genome-wide association study (GWAS) found strong associations between the BNAt phenotype and single-nucleotide polymorphisms (SNPs) on canine chromosome 1 (CFA1).…”
mentioning
confidence: 98%
See 3 more Smart Citations